2017
DOI: 10.2217/fvl-2016-0107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Phylogenic Study of Human T-lymphotropic Virus 1 in Patients With Thalassemia in the Northeast of Iran

Abstract: Aim: This study aimed to investigate the frequency and phylogenetic distribution of human T-lymphotropic virus type 1 (HTLV-1) in thalassemia cases. Methods: Between 2006 and 2013, a total of 100 thalassemic individuals were investigated for HTLV-1 infections. Results: Four people (4%) were reactive for HTLV antibodies. No considerable correlation was seen between factors such as age, blood transfusion history, surgery, marital status, gender and blood types. All HTLV-1 sequences belonged to the transcontinent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To the best of the best of our knowledge, no previous phylogenetic studies were conducted in Tehran and Urmia. Previous studies in Iran, such as Sabzevar, Torbat‐e Heydarieh, and Mashhad revealed that HTLV‐1 genotype belongs to the subtype a and the related subgroup was only reported in a recent study in Mashhad . Studied populations in these surveys were varied; studies about people born in Mashhad show that the HTLV‐1 genotype belongs to the cosmopolitan clade .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the best of our knowledge, no previous phylogenetic studies were conducted in Tehran and Urmia. Previous studies in Iran, such as Sabzevar, Torbat‐e Heydarieh, and Mashhad revealed that HTLV‐1 genotype belongs to the subtype a and the related subgroup was only reported in a recent study in Mashhad . Studied populations in these surveys were varied; studies about people born in Mashhad show that the HTLV‐1 genotype belongs to the cosmopolitan clade .…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to detect the provirus due to the rare proviral DNA expression in the infected host for some weeks, while the oncogenicity may be at high risk [3,4]. Human Immunodeficiency Virus (HIV) and Human T-cell lymphotropic virus (HTLV) are two kinds of human retroviruses that cause diseases with a high mortality potential [3,5,6]. Despite the joint transmission routes between HIV-1 and HTLV-1, they lead to remarkable different diseases.…”
Section: Introductionmentioning
confidence: 99%